A note on Selliguea murudensis (C. Chr.) Parris (Polypodiaceae), a new record of fern for Mount Alab, Crocker Range Park, Sabah - Luiza Majuakim; Florina Anthony (Institute for Tropical Biology and Conservation, 2016)
A rare fern species, Selliguea murudensis was found in the lower montane forest of Mount Alab. The species was previously observed in several localities, on Mount Kinabalu in Sabah and on Mount Mulu and Mount Murud in Sarawak. Mount Alab is the second locality of Selliguea murudensis to be recorded in Sabah, making it a new record for Mount Alab. Coincidentally, this was also the first record of the species to occur in higher altitude at 1,725 - 1900 m asl. The species is an epiphytic fern and was found growing on the trunk of a fallen tree. A single elongated fertile frond was observed with one series of sori on either side of the midvein. It thrives in cool, moist and shaded environment with air temperature and relative humidity of 15.5 ± 0.6 o C and 99.0 ± 2.1 %, respectively. The fern is believed to occur in abundance at Mount Alab and in the other localities of its limited distribution.